A hybrid-epistemological approach to climate change research: Linking scientific and smallholder knowledge systems in the Ecuadorian Andes. (March 2017) - López, Santiago; Jung, Jin-Kyu; López, María Fernanda
Abstract: Effective responses to the impacts of climate change require the recognition that people conceptualize and experience environmental changes differently, and require the support of a range of global-to-local interdisciplinary efforts that allow a dialog between the biophysical and social sciences. In this study, we use a hybrid epistemological framework that integrates scientifc and local knowledge systems, methodological approaches, and geographic scopes to: 1) shed light on climate change in the equatorial Andes as reported by scientific and local knowledge systems, and 2) understand the role that climate factors play on land use and agricultural change in natural resource dependent communities in the region. We analyzed weather station ( n =  5) data and downscaled climate data using parametric and non-parametric statistical tests, and spatial analysis techniques to detect spatio-temporal climate trends between 1965 and 2013. We also analyzed climate variability in the past four decades using qualitative information derived from a semi-structured survey ( n =  36) and life history smallholder interviews ( n =  8) collected in three research sites. Our study reveals significant warming trends in the region which is corroborated by local reports. Precipitation records show high inter-annual variability, with no significant decreasing or increasing trends, which contradicts people's views in two of our research sites. Our study shows that although climate change appears to be a factor that influences farmers' agricultural and livestock-production practices, other non-climatic forces play a more important role in determining their intensity and adoption. Despite site-level divergences and convergences, scientific and local knowledge systems can be woven together to expand our understanding of the physical and human manifestations of climate change.